UPAYA MENINGKATKAN KEAKTIFAN SISWA MELALUITALKING CHIPS MATERI UANG DAN PERBANKAN SISWA SMA ISLAMIYAH PONTIANAK - Kurniawati, Elis (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â Abstract This study aims to improve student activeness seen from student learning activities on money materials and banking class X A SMA Islamiyah Pontianak. This research is a Classroom Action Research consisting of four stages: (a) planning, (implementation), (observation), and (reflection). This research coalesced with economics teacher subjects conducted during the second cycle. Data were collected through observation sheets and student learning activity sheets. The result of the research that has been conducted shows that there is an increase of students' activity which is seen from the student's learning activity. Where in the first cycle the average physical activity is 56,7%, mental activity 53,3% and emotional activity 65%, while in cycle II average physical activity 75%, mental activity 73,3% and emotional activity 88,3% %. From cycle I to cycle II student learning activity has increased more than 60%. From the data obtained can be concluded that by using Talking Chips learning model can improve student activeness seen from student learning activities on money materials and banking class X A SMA Islamiyah Pontianak Keywords: Liveliness, Talking Chips,MoneyMaterials and Banking.